A Lacanian Approach to Medical Demand, With a Focus on Pediatric Genetics: A Plea for Subjectivization - Potier, Rémy; Putois, Olivier (Frontiers in Psychology, 2018)
Current psychological research on contemporary medicine, and in particular genetics, often targets the underpinnings of patients’ attitudes and behaviors with respect to biomedical knowledge and healthcare practices. But few studies approach these underpinnings as manifestations of the unconscious, while so doing could (in particular) help understand patients’ apparent difficulties to understand information, and to subsequently act accordingly (e.g. in making therapeutic decisions, etc.). We hypothesize that Lacan’s 1966 remarks (“The place of psychoanalysis in medicine”) on the transferential nature of the demand addressed by the patient (or his family) to the doctor can help account for these issues: demand filters medical information received from the practitioner, and thereby motivates subsequent decisions. In this paper, we try and shed light on this thesis, and focus on pediatric genetics. We start by describing the manifest doctor-patient-family relationship in the pediatric genetics consultation, in order to show where unconscious determinants can come to play a role (1). We then explain Lacan’s theory of demand: what the patient unknowingly demands is knowledge (savoir), the object of which is the body of jouissance – the libidinal experience of one’s body through the first libidinal exchanges with the Other of early infancy, whereby the subject is assigned by the Other (subjectification) a specific fantasmatic status organizing his desire. Patients’ understanding and attitudes thus vary so greatly because of this pre-existing filter. Healing and cure are merely apparent objects of the medical demand, which is an invocative drive seeking knowledge on the cause of one’s desire: medical demand is an instance of transference. Doctors should thus enable patient subjectivization, i.e. help them realize that their demand’s genuine object lies in their pre-existing subjective coordinates. (2) In pediatric genetics, apparently paradoxical family attitudes heavily draw on what G. Raimbault, drawing on Lacan, called implicit demand, the object of which is knowledge about the family fantasy giving shape to the guilt of possibly transmitting the disease. We give a clinical example, then show how the concept of demand helped us elaborate the core of a research project on the subjective effects of a genetic deafblindness handicap (3).